Assessing human impact on Rostherne Mere, UK, using the geochemistry of organic matter - Lacey, Jack H.; Leng, Melanie J.; Vane, Christopher H.; Radbourne, Alan D.; Yang, Handong; Ryves, David B. (Elsevier, 2018)
This study investigates recent changes in the geochemistry of organic material from a hypereutrophic lake (Rostherne Mere, United Kingdom) using the geochemical and molecular composition of radiometrically dated sediment cores. Modern samples suggest that recent sedimentation is dominated by algal production; however, a minor component of allochthonous organic material is present. Sediment cores reveal that absolute proxy values and the magnitude of observed changes are broadly homogenous across the lake basin. A transition to environmental conditions favouring enhanced algal productivity in recent sediments is suggested by higher total organic carbon (TOC) and lower carbon to nitrogen ratio (C/N), carbon isotope composition of organic matter (δ13Corg), and average n-alkane chain length. A strong covariance between TOC and Rock-Eval Hydrogen Index implies this transition is driven by an increasing algal contribution rather than being a response to variations in the source of organic matter. Decadal trends and abrupt shifts in organic geochemical proxies are suggested to be directly related to changes in external anthropogenic nutrient loading following the construction and decommissioning of sewage treatment plants. The development of hypereutrophic conditions likely occurred in stages, where rapid transitions are associated with the commencement of sewage effluent input in the 1930s, population increases in the 1980s, and a dramatic reduction in external nutrient loads in the 1990s. Recovery of the lake ecosystem is limited by internal nutrient recycling, and organic proxies indicate that the geochemistry of sediments has remained relatively constant since effluent diversion. This study highlights the utility of organic geochemical parameters in tracing recent eutrophication processes in lakes to provide evidence for the timing and scale of anthropogenic environmental change.